Recruitment of 7SL RNA to assembling HIV‐1 virus‐like particles. (1st December 2017) - Itano, Michelle S.; Arnion, Helene; Wolin, Sandra L.; Simon, Sanford M.
Abstract : Retroviruses incorporate specific host cell RNAs into virions. In particular, the host noncoding 7SL RNA is highly abundant in all examined retroviruses compared with its cellular levels or relative to common mRNAs such as actin. Using live cell imaging techniques, we have determined that the 7SL RNA does not arrive with the HIV‐1 RNA genome. Instead, it is recruited contemporaneously with assembly of the protein HIV‐1 Gag at the plasma membrane. Further, we demonstrate that complexes of 7SL RNA and Gag can be immunoprecipitated from both cytosolic and plasma membrane fractions. This indicates that 7SL RNAs likely interact with Gag prior to high‐order Gag multimerization at the plasma membrane. Thus, the interactions between Gag and the host RNA 7SL occur independent of the interactions between Gag and the host endosomal sorting complex required for transport (ESCRT) proteins, which are recruited temporarily at late stages of assembly. The interactions of 7SL and Gag are also independent of interactions of Gag and the HIV‐1 genome which are seen on the plasma membrane prior to assembly of Gag. Abstract : HIV‐1 infection and the associated disease AIDS are a major cause of human death worldwide with no vaccine or cure available. The assembly of virus particles involves numerous host and viral proteins that are potential therapeutic targets. We used high‐resolution microscopy techniques to investigate how the virus selectively incorporates a noncoding host RNA into virions budding from an infected cell. We show that 7SL RNA interacts with viral Gag proteins in the cytosol and arrives and accumulates with Gag at sites of viral assembly.